Hadith: (A woman whose three children die will be shielded by them from the Hell fire): Analytical study - Alibraheem, Hend Mohammed (Journal of Islamic Sciences, 2022)
The loss of children is one of the greatest misfortunes that Allah afflicts his servants with, and how hard would it be if it was the loss of more than one child! Therefore, it was from the grace of Allah upon his servants, Him offering the great reward to whom having that kind of misfortune with full patience when losing a child of his own.This research aims to show the virtue of patience, and the great reward waiting for those who lost one or more of their children but they have been patient and reckoning; and that is one of the reasons for entering Heaven, and being prohibited from Hell.The research concludes with showing the greatness of the reward of whom lost young children but has been patient and reckoning.The explanation of the importance of knowledge in Islam for both men and women, and that the woman seeks knowledge and science she needs to learn, and the people of knowledge should direct women, but rather they should single them out for education, like they direct men.This research is an analytical study of a Hadith whose main subject is: patience when loosing children, and the bitterness of pain and the darkness of loss that afflicts the soul, and sadness in the depths of the soul after losing the ones who are the adornment of life, and the reward and wage waiting for those who have been patient. Also, the eagerness of woman to acquire Islamic knowledge was mentioned in the Hadith.
Keywords: Patience; losing children; misfortune; woman and knowledge